ASPEN lipid injectable emulsion safety recommendations part 2: Neonate and pediatric considerations. (27th October 2021) - Cober, M. Petrea; Gura, Kathleen M.; Mirtallo, Jay M.; Ayers, Phil; Boullata, Joseph; Anderson, Collin R.; Plogsted, Steven; ,
Abstract: Lipid injectable emulsions (ILEs) are complex pharmaceutical formulations intended as a source of energy and fatty acids for parenteral nutrition (PN) therapy. Part 1 of this series addressed issues associated with and safety recommendations pertaining to adult ILE use. Part 2 addresses ILE safety in neonatal and pediatric patients. Considerations for ILE use in the neonatal and pediatric populations differ from those of adults. For example, these patients often require higher doses compared with adult counterparts to support growth, development, and daily metabolic needs. ILE is also frequently administered as a separate infusion as opposed to in a total nutrient admixture owing to compatibility and stability issues and limitations to intravenous access in the neonatal and pediatric populations. ILE is the most frequent PN ingredient associated with PN errors occurring in the administration, prescribing, and transcribing processes. Concerns exist with use of in‐line filters and repackaging of commercial products for infusion. ILE use in neonatal and pediatric patients has been associated with both minor and major adverse effects, which most often occur with doses exceeding manufacturer recommendations. Gaps in ILE best practices for neonatal and pediatric patients predispose to errors in the PN use system. This paper describes safe‐use considerations for ILE products available in the United States in neonatal and pediatric patients, including indications, prescribing, order review, preparation, administration, and monitoring. This paper has been approved by the American Society for Parenteral and Enteral Nutrition (ASPEN) Board of Directors.